2019
DOI: 10.4038/cmj.v64i3.8958
|View full text |Cite
|
Sign up to set email alerts
|

Association between visceral adiposity index, hirsutism and cardiometabolic risk factors in women with polycystic ovarian syndrome: A cross-sectional study

Abstract: Index words: adipocyte dysfunction, cardio-metabolic risk factors, hirsutism, polycystic ovarian disease, visceral adiposity index) 1 Abstract Introduction Visceral adiposity index (VAI) is a mathematical index derived from the body mass index (BMI), waist circumference (W C), serum fasting triglyceride (TG) and high-density lipoprotein cholesterol (HDL-C). It reflects visceral adipocyte dysfunction (VAD) and is associated with cardiometabolic risk. Women with polycystic ovarian syndrome (PCOS) have adipocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…We noted a positive correlation of VAI with systolic BP in PCOS women. Fonseka et al have also noted this correlation [18]. In our study, increasing VAI correlated significantly with greater mean ovarian volume and antral follicle count.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We noted a positive correlation of VAI with systolic BP in PCOS women. Fonseka et al have also noted this correlation [18]. In our study, increasing VAI correlated significantly with greater mean ovarian volume and antral follicle count.…”
Section: Discussionsupporting
confidence: 86%
“…It was noted that both fasting and post-prandial blood sugars correlated positively with VAI in PCOS women, a similar trend was seen with increasing VAI in non-PCOS women as well, albeit with weaker strength. An Asian study has similarly also observed a positive correlation between VAI and OGTT correlation [ 18 ]. Other authors have demonstrated that VAI correlates inversely with insulin sensitivity evaluated by the euglycemic hyperinsulinemic clamp test [ 10 ].…”
Section: Discussionmentioning
confidence: 96%
“…Exercise intensity, rather than exercise volume, seems to be the most important factor in improving health outcomes, according to a new metaanalysis. This data lends credence to the utility of exercise and it suggests that high-intensity workouts may have the largest influence on cardiorespiratory fitness, insulin resistance and body composition [28]. There was a moderate and high reduction in insulin resistance as evaluated by the HOMA-IR and body mass index (MD-0.57; 95% CI, 0.98 to 0.16 and p = 0.01; MD-1.90, 95% CI, 3.37 to 0.42 and p = 0.01) [29].…”
Section: Physical Activitysupporting
confidence: 55%
“…There was no significant association between parameters of hirsutism and the visceral adiposity index (VAI). Hirsutism is unlikely to be due to visceral adipocyte dysfunction [ 67 ]. Therefore, in PCOS patients with advanced obesity and/or obesity accompanied by full-blown metabolic syndrome, the introduction of a ketogenic diet may provide even better results than a diet with a LGI.…”
Section: Lifestyle Changesmentioning
confidence: 99%